Sosialisasi Dan Pemanfaatan Internet Guna Menarik Peluang Usaha Dimasa Pandemic Covid-19 Kepada Masyarakat Jombang Kramat - Hermawan; Aldianur Muhammad Herjendi; Bimas Febriana Putra; Danang Prasetio Adi; Fajar Budiman; Galih Ilham Setiaji; Putra Agustiansyah; Rizza Nurul Hidayat; Seno Ariadi (CV. Multi Kreasi Media, 2023)
The definition of Marketing is a system for carrying out marketing activities as a whole starting from product planning, pricing, promotion to designing product distribution strategies to satisfy consumers. Today, we must often hear the word Internet and we tend to be more familiar with terms such as E-Commerce, E-government and others. The letter